Local innovation ecosystem: structure and impact on adaptive capacity of firms. Issue 5 (28th May 2021) - Boyer, James; Ozor, Jude; Rondé, Patrick
ABSTRACT: Focusing on the Local Innovation Ecosystem in Hauts-de-France region (France), the aim of this paper is to analyse how the ecosystems affect firm's adaptive capacity. First, we show these local innovation ecosystems are based on Innovation Parks . They promote knowledge development and innovation processes by bringing together heterogeneous agents such as research laboratories, technological structures, finance organisations, brokers, start-ups, and companies within a complex interacting and strategic context. Second, we use econometric models to test the impact of these local innovation ecosystems on the innovativeness and technological diversity of firms viewed as components of adaptive capacity. Our results show that firms belonging to local innovation ecosystems centred on innovation parks are both more innovative and more technologically diversified than others. Our study suggests further empirical research in order to specify links between the most relevant characteristics of the innovation ecosystem and the firm's adaptive capacity.